Evaluation of Waste Stabilization Pond Efficiency and Its Effluent Water Quality: a Case Study of Kito Furdisa Campus, Jimma University, Southwest Ethiopia - Belay Desye; Biniam Belete; Embay Amare Alemseged; Yonas Angaw; Zinabu Asfaw Gebrezgi (The Scientific World Journal)
Waste stabilization pond (WSP) technology is one of the most promising wastewater treatment methods. In developing countries, including Ethiopia, only a small proportion of the wastewater is being treated. Discharge of untreated wastewater into receiving water bodies may lead to disruption of ecological integrity, economic, and public health risks. However, there is limited evidence on WSP efficiency and effluent water quality in Ethiopia. A laboratory-based cross-sectional study was conducted on 60 wastewater samples. A standard method of procedure was used to collect and analyze samples. SPSS version-24 was used for statistical analysis and a paired t-test was used to test for statistical significant differences. A statistically significant difference (p<0.001) in the removal efficiency of BOD5 up to 75.3% (117 mg/L effluent) and COD up to 56.5% (457.5 mg/L effluent) was recorded. A statistically significant difference (p<0.001) in the removal efficiency of TN up to 79% (17.4 mg/L effluent), TP up to 69.2% (4.8 mg/L effluent), and PO4−3 up to 71% (3.36 mg/L effluent) was recorded. Whereas, a statistically significant difference (p<0.001) in the removal efficiency of total coliforms up to 99.99% (3.4 × 103 MPN/100 mL effluent) and fecal coliforms up to 94.3% (8.54 × 102 MPN/100 mL effluent) was recorded. The overall efficiency of the treatment plant was 73.5% and its water quality index of the effluent water quality of WSP was 30. The finding showed that the efficiency of the WSP was judged as satisfactory and the effluent water quality of WSP is unsuitable for the discharge into the environment. Therefore, to improve the efficiency of the WSP and to produce adequately treated water, it required adequate preliminary treatment, modification of the design, desludging of the pond, additional treatment, and frequent monitoring and maintenance of the pond.